ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN MATA PELAJARAN AKUNTANSI DI KELAS X AKUNTANSI SMK NEGERI 1 JOMBANG - IIS TRY ALFIYANI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Media learning is an auxiliary apparatus can be used by teachers as a link or communications among teachers with students in conveying information. The purpose of this research is to find out: ( 1 ) media learning and reasons used the teacher (2) the media feasibility study on the subjects (3) the response to media students learning. This research is research descriptive by kuantitatif approach. Technical data that used technique interview documentation and poll examine media experts and response graders x accounting 3.Research results revealed teachers use learning media is white board, job sheet, and power point or frame of film (slides). Reasons to use media power point as it can support and facilitate teachers in delivering the material Accounting to students. Average research learning media feasibility the learning subjects in Accounting rating 65,38% with category viable and the X-grade Accounting student response 3 about the use of the media learning gained an average rating of 75,61% criteria agreed. Those it can be concluded that the use of the media learning subjects in Accounting class 3 Accounting X SMK negeri 1 Jombang is feasible. Keywords:the media, learning subjects accounting